Trends in Positive Life Orientation Among 70-Year-Olds: A Comparison of Two Finnish Cohorts Born 20 Years Apart - Langén, Ville L. (Taylor & Francis, 2025)
Objectives: We assessed if positive life orientation (PLO) has increased among older individuals and explored gender disparities in PLO changes.
Methods: Two cohorts of 70-year-olds from Turku, Finland were included: the 1920 birth cohort (examined in 1991; n = 1,032) and the 1940 birth cohort (examined in 2011; n = 956). Participants completed an identical questionnaire assessing life satisfaction, feeling needed, future plans, zest for life, depression, and loneliness. A composite PLO score (range 0-1) was computed.
Results: The 2011 cohort had a higher mean PLO score than the 1991 cohort (.87 vs. .83, p < .001). The 2011 cohort reported higher sense of being needed, more future plans, and reduced loneliness (all p < .001). No significant differences were found in life satisfaction, zest for life, or depression. Gender disparities in PLO persisted across both cohorts, with men scoring slightly higher but following similar trends as women.
Discussion: PLO appears to have increased among older individuals.
Clinical implications: Recognizing the rising trend of PLO in recent decades may influence the development of societal and healthcare policies to further improve overall well-being among older individuals.